До проблеми визначення сутності спортивного права - Харитонов, Євген Олегович; Харитонов, Є. О.; Kharytonov, Yevhen O.; Харитонова, Олена Іванівна; Харитонова, О. І.; Kharytonova, Olena I. (Одеса, 2018)
У статті досліджуються проблеми визначення сутності спортивного права. На підставі аналізу особливостей зазначеного правового феномену зроблено висновок, що спроби визначити «спортивне право» з погляду нормативістського праворозуміння не дають позитивного результату. Обґрунтована доцільність характеристики спортивного права як концепту, тобто як сукупність уявлень, понять, знань, асоціацій, емоцій, що виникають у зв’язку з правовим впорядкуванням суспільних відносин у галузях, що стосуються спорту. Розгляд «спортивного права» як концепту, не заперечує «нормативного» наповнення цього поняття, але позбавляє необхідності оцінки його як системи правових норм, що утворюють жорстку ієрархічну структуру. При цьому головним критерієм віднесення нормативного акту до «спортивного права», котре є комплексною галуззю законодавства, є предмет правового регулювання.

The article deals with the problems of determining of the essence of sports law. The points of view on the concept of sports law and attempts to characterize it as a special field of law, a special field of legislation, a complex branch of law, and a complex field of legislation are analyzed. Based on the analysis of the views of legal scholars in scientific works, it is concluded that the definition of sports law as an area of law (legislation) is hopeless, since this branch should have its own subject and method of legal regulation. This statement is based on the peculiarities of understanding of the field of law (legislation) as a part of the legal system, “normative” understanding of law. But if the subject of “sports law” is defined quite simply (it is – “sports relations”), then the method of legal regulation cannot be named precisely. This is explained by the fact that sports relationships can arise in different spheres, and regulated by different ways of legal influence (both imperative and dispositive). The expediency of the characterization of sports law as a concept, as a set of ideas, knowledge, associations, emotions that arise in connection with the legal regulation of social relations, in the branch (es) concerned with sport, is substantiated in the article. Consideration of “sports law” as a concept does not deny the “normative” content of this concept, but eliminates the need to evaluate it as a system of legal rules that form a rigid hierarchical structure. At the same time, the main criterion for assigning a normative act to “sports law”, which is a complex branch of legislation, is the subject of legal regulation – sports relations. It is proposed to distinguish “sports relations” and “relations that arise in the field of sport”. The main difference between them is that “sports relationships” cannot exist outside the sport (for example, relations related to the organization and conduct of sports events, the relationship of recreational physical education, fitness, etc.), and if they exist, they acquire this sphere of essential features, due to the properties of the sphere.
Харитонов Є. О. До проблеми визначення сутності спортивного права / Є. О. Харитонов, О. І. Харитонова // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Одеса, 2018. – Вип. 30. – С. 6-10.
Keywords: спорт; спортивне право; нормативне праворозуміння; концепт; галузь права; галузь законодавства; sport; sports law; normative understanding of law; concept; branch of law; branch of legislation; Research Subject Categories::LAW/JURISPRUDENCE